Leveraging VOIP on Local Area Network using Java Media Framework (A case study of Kumasi Technical Institute) - Asante, George (2016)
A thesis submitted to the Department of Computer Science, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirements for the Degree of Master of Philosophy in Information Technology. College of Science. June 2012.